Tanggapan Mahasiswa Hukum Unisba Terhadap Website Lembaga Bantuan Hukum Bandung - Hana Rengganawati (Program Studi Hubungan Masyarakat Politeknik LP3I, 2023)
The research entitled Responses of Unisba Students to the Bandung Law Institute Website (Case Study on the Bandung Legal Aid Institute's Website www.lbhbandung.org) was driven by the development of information media, especially websites. This study aims to determine the responses of Unisba students to the LBH Bandung website by observing the object of research, namely the Bandung Legal Aid Institute Website regarding content quality, content availability, message content consistency and visual appearance of the Bandung Legal Aid Valley website. This research uses a qualitative descriptive method and a collection method with interviews, observation, and literature studies. The results showed that the majority of respondents stated that the information about LBH Bandung organizations displayed on www.lbhbandung.org was in accordance with the needs of visitors. This is because on this website all information related to LBH Bandung from history, organizational profiles, cases that have been resolved, organizational structure and anything related to LBH Bandung's organization has been displayed in full according to the needs of visitors. The results showed that the quality of the message content, the availability of the message content, the consistency of the content and the visual appearance of the website greatly influenced the positive response and attractiveness of website visitors, especially students.